Against the fire - Martin, Kat (Don Mills, Ont. : MIRA, 2011)
"You can't fight what you can't see. And Gabriel Raines can't be sure just who's setting the fires in his new real -estate development. When two fires hit back-to-back, he knows it's personal, but any number of competitors or ex- employees could be the arsonist. The police suspect Angel Ramirez, a local teen who's been in trouble before. But Mattie Baker, a volunteer at the Family Abuse center, just can't believe the kid she's been working with would go back to his delinquent ways. Determined to convince Gabe that she's right, Mattie must get close to him and find out who's putting their neighborhood in jeopardy. And just as the arsonist's flames continue to burn, they find a heat developing between them. It might just turn into a full-fledged fire...if they can survive long enough."--P. [4] of cover
Keywords: Real estate developers -- Fiction; Arson -- Fiction; Arson investigation -- Fiction; Wyoming -- Fiction